Sensitivity analysis of reactor and distillation column of paraxylene plant via toluene methylation based on simulation process - Prasetiawan, H.; Fardhyanti, Dewi Selvia; Sumaiya, Zainal Abidin (Semarak Ilmu Publishing, 2025)
Paraxylene is an important industrial compound, and its demand has been increasing in recent years.Paraxylene is made in several processes, one of which is toluene methylation. Furthermore,it is necessary to do a simulation to determine the optimal operating conditions in the formation and separation of paraxylene. The simulation was done using process simulation software. The first research design scheme was data validation. The results of the data validation obtained 3 –4 % error indicatedthat the simulationwas validated and can be used for the next step which is sensitivity analysis.The sensitivity analysis was performed to obtainthe optimumreactor and column configuration. Based on the simulation of paraxylene production throughtoluene methylation process, the obtained purity was over95%. The temperature and pressure of the reactor feed 600°C and 7 bar were obtained, the weight of the catalyst was 15,000 kg, the ratio of the catalyst feed to the toluene feed 37, and the ratio of the toluene feed to methanol 2. The optimal feed stage was obtained at the 18 stage, the number of stages was 27, the load a reboiler of 18,000 kW, and a reflux ratio of 2.